A moral e o progresso do gênero humano na história em Kant - Alves, Keine (2023)
This dissertation aims to expose the aspects surrounding the Kantian conception of universal history. Therefore, the objectives of this dissertation also consisted in elucidating the different conceptions of history; the relation between morality and progress in history, as presented by Kant; the elucidation of how morality can be a determining factor for human progress; the clarification of the relevance of Kant's ideas for the formation of his philosophy of history, as well as the understanding of the relation between morality and progress in society. To achieve these objectives, the following topics were addressed: the idea of a cosmopolitan purpose in history, according to Kant; the aspects of the relationship between morality and the achievement of this purpose; the conception of progress in Kant's work; the importance of the aspects of morality for human progress; the problem of the different conceptions of history as well as the idea of juridical progress. Thus, the methodological procedure employed was bibliographical research, using only proper books as a research reference, whose temporal period does not exceed the last 50 years. Based on the research done, this study analyzed Kantian thought, exploring the conceptions of time and the role of history in the moral and legal development of mankind, initially addressing the path of enlightenment and the role of history in Kantian philosophy. By discussing different conceptions of time, such as cyclical and linear time, the dissertation analyzes how Kant reconciled these views and how this affected his understanding of human progress and, in this context, Kant's quest for a factual and universal history is analyzed. The dissertation also explored how Kant based his understanding of progress in history on concrete facts and on a perspective that could be applied to all human beings, regardless of their cultural or geographical differences, also evaluating, according to Kant, the conduction to historical evolution through morality and the search for a cosmopolitan history that moves in the same direction, contemplating also the legal evolution in the philosophy of the Enlightenment, the idea of law and contractualism, because, Kant conceived progress in the legal field, as an integral part of moral development and how it is connected to the evolution of humanity, which is analyzed as a result of external freedom, morality and legality, conceiving external freedom as a necessary condition for this. In sum, this dissertation offers a deep and detailed analysis on Kantian conception of universal history, exploring as a consequence the relationship between morality, progress and history addressed in the philosopher's thought and, by examining issues such as conceptions of time, factual and universal history, legal and moral progress, and the importance of external freedom, morality and legality, it is understood that the study contributes significantly to the understanding of Kant's view on the moral and legal evolution of humanity throughout history